Data fusion protocol with source security for sensor networks - ZHANG Peng; YU Jian-ping; LIU Hong-wei (Tongxin xuebao)
For the source security need,a digital signature scheme with aggregate signatures,data fusion and batch verification was proposed.Based on the proposed signature scheme and the homomorphic encryption technology,a data fusion protocol with secure sources was advanced.Security analyses show that the proposed signature scheme is secure based on the CDH assumption,and the proposed protocol can provide the collected data end-to-end confidentiality and authentication.